Inhibition of calcineurin combined with dasatinib has direct and indirect anti‐leukemia effects against BCR‐ABL1+ leukemia. Issue 9 (19th June 2014) - Gardner, Lori A.; Klawitter, Jelena; Gregory, Mark A.; Zaberezhnyy, Vadym; Baturin, Dmitry; Pollyea, Daniel A.; Takebe, Naoko; Christians, Uwe; Gore, Lia; DeGregori, James; Porter, Christopher C.
<x xml:space="preserve">Abstract</x> Treatment of BCR‐ABL1+ leukemia has been revolutionized with the development of tyrosine kinase inhibitors. However, patients with BCR‐ABL1+ acute lymphoblastic leukemia and subsets of patients with chronic myeloid leukemia are at high risk of relapse despite kinase inhibition therapy, necessitating novel treatment strategies. We previously reported synthetic lethality in BCR‐ABL1+ leukemia cells by blocking both calcineurin/NFAT signaling and BCR‐ABL1, independent of drug efflux inhibition by cyclosporine. Here, using RNA‐interference we confirm that calcineurin inhibition sensitizes BCR‐ABL1+ cells to tyrosine kinase inhibition in vitro. However, when we performed pharmacokinetic and pharmacodynamic studies of dasatinib and cyclosporine in mice, we found that co‐administration of cyclosporine increases peak concentrations and the area under the curve of dasatinib, which contributes to the enhanced disease control. We also report the clinical experience of two subjects in whom we observed more hematopoietic toxicity than expected while enrolled in a Phase Ib trial designed to assess the safety and tolerability of adding cyclosporine to dasatinib in humans. Thus, the anti‐leukemia benefit of co‐administration of cyclosporine and dasatinib is mechanistically pleiotropic, but may not be tolerable, at least as administered in this trial. These data highlight some of the challenges associated with combining targeted agents to treat leukemia. Am. J. Hematol. 89:896–903, 2014. © 2014 Wiley Periodicals, Inc.